The adenosine triphosphatase-inhibitor content of bovine heart submitochondrial particles. Influence of the inhibitor on adenosine triphosphate-dependent reactions. - Ferguson, S J (1977)
1. The activity of the ATPase (adenosine triphosphatase) of phosphorylating particles prepared by sonication of bovine heart mitochondria in the presence of MgCl2 and ATP is influenced by the isolation method for the mitochondria used in the preparation of particles. Type-I particles, made from mitochondria isolated in a medium lacking succinate, have a lower ATPase activity than to Type-II particles, which are prepared from mitochondria isolated in a medium containing succinate. 2. Centrifugation under appropriate energized conditions increases the ATPase activity of Type-I particles almost to that of the Type-II particles. The ATPase activity of Type-II particles was only slightly stimulated by this procedure. These data are interpreted as indicating a higher content of the ATPase-inhibitor protein in the Type-I particles. 3. A comparison was made of the ATP-driven enhancement of 8-anilinonaphthalene-1-sulphonate fluorescence and the exchange of the endogenous tightly bound nucleotides of the ATPase in Type-I and Type-II particles. The effect of exogenous inhibitor protein on both these reactions was also studied. 4. The time-scale on which the inhibitor protein can exchange between ATPase molecules is discussed.